Galicia Dixital. Una exposición de patrimonio e-tangible. El Museo Vacío. - Luis A. Hernández Ibáñez (Virtual Archaeology Review)
Galicia Dixital is an exhibition located in Santiago de Compostela whith the mission to show the culture and heritage of this region through the use of new audiovisual technologies, whilst to demonstrate the use and applications of avant-garde technology. This paper describes some of the installations present there with special emphasis in The Empty Museum, a fully immersive virtual reality installation where the user can walk physically visiting virtual worlds. A group of examples of contents designed for this medium will be also described.